From Synthesis to Application: Structure, Properties, and Photocatalytic Efficacy of CuFe2O4 Nanocomposites by Co-precipitation Method - Samah Rebhi (My University, 2026)
The environment is severely affected by the increasing number of pollution sources, particularly industrial discharges rich in toxic organic compounds such as dyes. In response to this issue, several depollution techniques have been developed. Among them, photocatalysis has emerged as an effective and innovative method for the removal of pollutants from wastewater. In this work, we focus on the synthesis of CuFe₂O₄ nanocomposites, which are semiconductor materials exhibiting excellent structural, magnetic, and photocatalytic properties. The main objective of this study is to evaluate their efficiency in the degradation of Malachite Green dye in an aqueous medium. The synthesized CuFe₂O₄ nanocomposites were characterized using various physicochemical techniques, including X-ray diffraction (XRD), scanning electron microscopy coupled with EDS analysis (SEM-EDS), and Fourier Transform Infrared Spectroscopy (FTIR), in order to investigate their structure, morphology, and composition. The photocatalytic activity was studied by analyzing the influence of several experimental parameters, such as the catalyst mass....The obtained results show a significant photocatalytic activity of the synthesized CuFe₂O₄ nanocomposites, with optimized performance under well-defined experimental conditions, thus confirming their potential for environmental applications in polluted water treatment. --------------------------------------------------------------------- البيئة تتأثر بشكل كبير بتزايد مصادر التلوث، خاصةً المخلفات الصناعية الغنية بالمركبات العضوية السامة مثل الأصبغة. وأمام هذه الإشكالية، تم تطوير عدة تقنيات لمعالجة التلوث، ومن بينها تبرز تقنية التحفيز الضوئي باعتبارها طريقة فعّالة ومبتكرة لإزالة الملوثات من المياه المستعملة. في هذا العمل، نهتم بتحضير المركبات النانوية CuFe₂O₄، وهي مواد شبه موصلة تتميز بخصائص بنيوية ومغناطيسية وتحفيزية ضوئية ممتازة. ويتمثل الهدف الرئيسي لهذه الدراسة في تقييم فعاليتها في تحلل صبغة أخضر المالاكيت في الوسط المائي. تم توصيف المركبات النانوية CuFe₂O₄ المحضّرة باستعمال عدة تقنيات فيزيائية-كيميائية، من بينها حيود الأشعة السينية (DRX)، والمجهر الإلكتروني الماسح المقترن بتحليل EDS ‏(MEB-EDS)، بالإضافة إلى التحليل بالأشعة تحت الحمراء بتحويل فورييه (FTIR)، وذلك لدراسة بنيتها، ومورفولوجيتها، وتركيبها الكيميائي. تمت دراسة النشاط التحفيزي+ الضوئي من خلال تحليل تأثير عدة عوامل تجريبية، مثل كتلة المحفّز... أظهرت النتائج المتحصل عليها نشاطًا تحفيزيا ضوئيا ملحوظًا للمركبات النانوية CuFe₂O₄ المُحضّرة، مع أداء مُحسَّن تحت ظروف تجريبية محددة جيدًا، مما يؤكد إمكاناتها في التطبيقات البيئية الخاصة بمعالجة المياه الملوثة. ------------------------------------------------------------------- L’environnement est fortement affecté par la multiplication des sources de pollution, notamment les rejets industriels riches en composés organiques toxiques tels que les colorants. Face à cette problématique, plusieurs techniques de dépollution ont été développées. Parmi elles, la photocatalyse s’impose comme une méthode efficace et innovante pour l’élimination des polluants dans les eaux usées. Dans ce travail, nous nous intéressons à la synthèse des nanocomposites CuFe₂O₄, des matériaux semi-conducteurs présentant d’excellentes propriétés structurales, magnétiques et photocatalytiques. L’objectif principal de cette étude est d’évaluer leur efficacité dans la dégradation du colorant Vert de Malachite en milieu aqueux. Les nanocomposites CuFe₂O₄ obtenus ont été caractérisés à l’aide de différentes techniques physico-chimiques, notamment la diffraction des rayons X (DRX) et la microscopie électronique à balayage couplée à l’EDS (MEB-EDS), et spectroscopie infrarouge à transformée de Fourier (FTIR), afin d’étudier leur structure, leur morphologie et leur composition. L’activité photocatalytique a été étudiée en analysant l’influence de plusieurs paramètres expérimentaux, tels que la masse du catalyseur.... Les résultats obtenus montrent une activité photocatalytique significative des nanocomposites CuFe₂O₄ synthétisés, avec des performances optimisées dans des conditions expérimentales bien définies, confirmant ainsi leur potentiel pour des applications environnementales dans le traitement des eaux polluées.
Keywords: Photocatalysis; CuFe₂O₄ nanocomposites; Malachite Green degradation; characterization.; التحفيز الضوئي، المركبات النانوية CuFe₂O₄ ، تحلل أخضر المالاكيت، التوصيف.; Photocatalyse; Nanocomposites CuFe₂O₄; Dégradation du vert de malachite; Caractérisation.